Identification of Genetic Risk Factors for Maxillary Lateral Incisor Agenesis. (May 2014) - Alves-Ferreira, M.; Pinho, T.; Sousa, A.; Sequeiros, J.; Lemos, C.; Alonso, I.
Tooth agenesis affects 20% of the world population, and maxillary lateral incisors agenesis (MLIA) is one of the most frequent subtypes, characterized by the absence of formation of deciduous or permanent lateral incisors. Odontogenesis is a complex mechanism regulated by sequential and reciprocal epithelial-mesenchymal interactions, controlled by activators and inhibitors involved in several pathways. Disturbances in these signaling cascades can lead to abnormalities in odontogenesis, resulting in alterations in the formation of the normal teeth number. Our aim was to study a large number of genes encoding either transcription factors or key components in signaling pathways shown to be involved in tooth odontogenesis. We selected 8 genes— MSX1, PAX9, AXIN2, EDA, SPRY2, TGFA, SPRY4, and WNT10A —and performed one of the largest case-control studies taking into account the number of genes and variants assessed, aiming at the identification of MLIA susceptibility factors. We show the involvement of PAX9, EDA, SPRY2, SPRY4, and WNT10A as risk factors for MLIA. Additionally, we uncovered 3 strong synergistic interactions between MLIA liability and MSX1 - TGFA, AXIN2 - TGFA, and SPRY2 - SPRY4 gene pairs. We report the first evidence of the involvement of sprouty genes in MLIA susceptibility. This large study results in a better understanding of the genetic components and mechanisms underlying this trait.